The crime of collusion as agreement and execution: notes from basic foundations of the theory of crime - Guimaray, Erick (2024)
From an eminently factual point of view, in almost all cases of public corruption there is a pact between public officials and private individuals, in which public interests are subordinated to personal desires. However, paradoxically, in the crime of collusion, this pact is not sufficient to justify criminal intervention until it is carried out. This new interpretation of the crime has important consequences for key institutions of the theory of crime, such as the criminal risk to the legal interest, the typical behavior or the system of criminal intervention. Thus, this work attempts to show the systematicity between the proposed interpretation and its legal consequences, hand in hand with basic questions of the theory of crime.